Linear dichroism infrared resonance in overdoped, underdoped, and optimally doped cuprate superconductors - Mukherjee, A.; Seo, J.; Arik, M. M.; Zhang, H.; Zhang, C. C.; Kirzhner, T.; George, D. K.; Markelz, A. G.; Armitage, N. P.; Koren, G.; Wei, J. Y. T.; Cerne, J. (Physical Review B, 2020)
By measuring the polarization changes in terahertz, infrared, and visible radiation over an extended energy range (3-2330 meV), we observe symmetry breaking in cuprate high-temperature superconductors over wide energy, doping, and temperature ranges. We measure the polarization rotation (Re[theta(F)]) and ellipticity (Im[theta(F)]) of transmitted radiation through thin films as the sample is rotated. We observe a twofold rotational symmetry in theta(F), which is associated with linear dichroism (LD) and occurs when electromagnetic radiation polarized along one direction is absorbed more strongly than radiation polarized in the perpendicular direction. Such polarization anisotropies can be generally associated with symmetry breakings. We measure the amplitude of the LD signal and study its temperature, energy, and doping dependence. The LD signal shows a resonant behavior with a peak in the few hundred meV range, which is coincident with the midinfrared optical feature that has been associated with the formation of the pseudogap state. The strongest LD signal is found in underdoped films, although it is also observed in optimally and overdoped samples. The LD signal is consistent with an electronic nematic order which is decoupled from the crystallographic axes as well as novel magnetoelectric effects.
Keywords: Materials Science; Physics

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Evidence of protein collective motions on the picosecond timescale - He, Yunfen; Chen, J-Y; Knab, Joseph R; Zheng, Wenjun; Markelz, Andrea G (Biophysical Journal, 2011)

Why is THz Sensitive to Protein Functional States? Oxidation State of Cytochrome C - He,Y.; Chen, J.-Y.; Knab, J. R.; Zheng, W.; Markelz, A.G. (Terahertz Science and Technology, 2010)
We investigate the presence of structural collective motions on a picosecond time scale for the heme protein, cytochrome c, as a function of oxidation and hydration, using terahertz (THz) time-domain spectroscopy and molecular dynamics simulations. Structural collective mode frequencies have been calculated to lie in this frequency range, and the density of states can be considered a measure of flexibility. A dramatic increase in the THz response occurs with oxidation, with the largest increase for lowest hydrations and highest frequencies. For both oxidation states the measured THz response rapidly increases with hydration saturating above ~25% (g H2O/g protein), in contrast to the rapid turn-on in dynamics observed at this hydration level for other proteins. Quasi-harmonic collective vibrational modes and dipole-dipole correlation functions are calculated from the molecular dynamics trajectories. The collective mode density of states alone reproduces the measured hydration dependence providing strong evidence of the existence of these collective motions. The large oxidation dependence is reproduced only by the dipole-dipole correlation function, indicating the contrast arises from diffusive motions consistent with structural changes occurring in the vicinity of a buried internal water molecule.

Terahertz spectroscopy of bacteriorhodopsin and rhodopsin: Similarities and differences - Balu, R.; Zhang, H.; Zukowski, E.; Chen, J. Y.; Markelz, A. G.; Gregurick, S. K. (Biophysical Journal, 2008)
We studied the low-frequency terahertz spectroscopy of two photoactive protein systems, rhodopsin and bacteriorhodopsin, as a means to characterize collective low-frequency motions in helical transmembrane proteins. From this work, we found that the nature of the vibrational motions activated by terahertz radiation is surprisingly similar between these two structurally similar proteins. Specifically, at the lowest frequencies probed, the cytoplasmic loop regions of the proteins are highly active; and at the higher terahertz frequencies studied, the extracellular loop regions of the protein systems become vibrationally activated. In the case of bacteriorhodopsin, the calculated terahertz spectra are compared with the experimental terahertz signature. This work illustrates the importance of terahertz spectroscopy to identify vibrational degrees of freedom which correlate to known conformational changes in these proteins.
Keywords: Biophysics; bovine rhodopsin; conformational-changes; elastic; frequency normal-modes; light activation; molecular-dynamics simulation; neutron-scattering; protein-coupled receptors; transmembrane helices; vibrational-modes; wild-type

Terahertz transmission characteristics of high-mobility GaAs and InAs two-dimensional-electron-gas systems - Kabir, N. A.; Yoon, Y.; Knab, J. R.; Chen, J. Y.; Markelz, A. G.; Reno, J. L.; Sadofyev, Y.; Johnson, S.; Zhang, Y. H.; Bird, J. P. (Applied Physics Letters, 2006)
Frequency-dependent complex conductivity of high-mobility GaAs and InAs two-dimensional-electron-gas (2DEG) systems is studied by terahertz time domain spectroscopy. Determining the momentum relaxation time from a Drude model, the authors find a lower value than that from dc measurements, particularly at high frequencies/low temperatures. These deviations are consistent with the ratio tau(t)/tau(q,) where tau(q) is the full scattering time. This suggests that small-angle scattering leads to weaker heating of 2DEGs at low temperatures than expected from dc mobilit9y. (c) 2006 American Institute of Physics.
Keywords: field-effect transistors; photoconductivity; Physics; plasma-waves; radiation; resonant detection; subterahertz

Direct measurements of optical phonons in SrTiO3 nanosystems - Wolpert, D; Korolev, K; Sachs, S; Knab, J; Cox, W; Cerne, J; Markelz, A.G; Zhao, T; Ramesh, R; Moeckly, B.H (Physica E: Low-dimensional Systems and Nanostructures, 2003)
We use terahertz time domain spectroscopy to examine finite size effects on the optical phonon modes in SrTiO3 thin films. In temperature-dependent measurements we find a near absence of mode softening in the TO1 phonon frequency. Furthermore we see an increase in the soft mode frequency with reduced thickness. Both of these results correlate well with the reduced dielectric response observed for nanoscale ferroelectric systems.
Keywords: Ferroelectrics; Finite size; Mode softening; phonons; Strontium titanate; Terahertz

Finite size effects in ferroelectric nanosystems: Absence of mode softening - D. Wolpert; W. Cox; J. Cerne; A. Markelz; T. Zhao; R. Ramesh (2003 Nanotechnology Conference and Trade Show - Nanotech, 2003)
We present measurements of the mode softening behavior for PbZr 0.5Ti0.5O3 (PZT(50)) thin films using terahertz time domain spectroscopy (TTDS). The films were grown using pulsed laser deposition (PLD) techniques on silicon substrates to study how reduced size affects the mode softening behavior. At room temperature two modes are observed at 1.1 THz (37 cm-1) and at 2.3 THz (77 cm-1). As the temperature is increased toward Tc we do not see strong mode softening, but rather a spectral weight transfer from the high frequency mode to the low frequency mode. This absence of mode softening is more dramatic than that reported by other investigators[1]. We will discuss the possible sources for this discrepancy. These results suggest a change in lattice dynamics for nanoscale ferroelectric films that may be highly dependent on the sample preparation technique.
Keywords: Ferroelectric materials; Fourier Transform Infrared Spectroscopy; Frequency ranges; Lead compounds; Mode softening; nanostructured materials; Natural frequencies; Optical modes; Permittivity; phase transitions; phonons; Routers; Thermal effects